Analisa Kemampuan PT. PAL Indonesia dalam Membangun Alutsista TNI Terhadap Operasi Penanggulangan Bencana Alam dengan Menggunakan SPSS - Roma Gunawan; Benny Limbong; Agus Soeprianto (Jurnal Sosial Teknologi, 2026)
As the world's largest archipelagic country situated at the junction of three major tectonic plates and the Pacific Ring of Fire, Indonesia faces high natural disaster risks. This requires defense equipment that can be operated effectively by various TNI branches in disaster response operations. The research employs a quantitative approach with descriptive and causality methods. Data analysis utilized multiple linear regression with SPSS version 29. Validity and reliability testing of instruments, as well as classical assumption tests, were conducted to ensure the validity of research results. The findings show that: (1) Human resource qualifications at PT. PAL Indonesia positively influence TNI interoperability with a regression coefficient of 0.150 and significance value of 0.059 (significant at α=0.10); (2) Technology transfer has a positive influence with a regression coefficient of 0.262 and significance value of 0.007; (3) Stakeholder coordination has the most dominant influence with a regression coefficient of 0.488 and significance value of 0.000; (4) The three variables simultaneously have a significant influence on TNI interoperability with F=72.028 and R²=0.647, meaning 64.7% of the variation in TNI interoperability can be explained by these three variables. Descriptive analysis results indicate that work experience of PT. PAL Indonesia personnel has the highest value (4.21), while the number of experts has the lowest value (3.81). For the technology transfer variable, cooperation with foreign industries has the highest value (4.25), while production licensing has the lowest value (3.85). For stakeholder coordination, joint evaluation has the highest value (4.22), while routine communication has the lowest value (3.89). For the interoperability variable, equipment supporting joint operation capabilities has the highest value (4.05), while standardized data formats between branches has the lowest value (3.75).